Involution rings with unique minimal *-biideal - Mendes, D.I.C. (Algebra and Discrete Mathematics, 2016)
The structure of certain involution rings which have exactly one minimal *-biideal is determined. In addition, involution rings with identity having a unique maximal biideal are characterized.